1997
DOI: 10.1046/j.1471-4159.1997.69052005.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Thiamine Diphosphate Levels in Brains of Patients with Frontal Lobe Degeneration of the Non‐Alzheimer's Type

Abstract: Abstract:We compared the thiamine and thiamine phosphate contents in the frontal, temporal, parietal, and occipital cortex of six patients with frontal lobe degeneration of the non-Alzheimer's type (FNAD) or frontotemporal dementia with five age-, postmortem delay-, and agonal status-matched control subjects. Our results reveal a 40-50% decrease in thiamine diphosphate (TDP) in the cortex of FNAD patients, whereas thiamine monophosphate was increased 49-119%. TDP synthesizing and hydrolyzing enzymes were unaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(48 reference statements)
0
7
1
Order By: Relevance
“…Such a mechanism could help to better understand the events involved in the onset of neurodegenerative diseases (64). It is therefore interesting to point out that thiamine deficiency has been shown to exacerbate the pathology of Alzheimer disease (63,65,66) and that there are dysfunctions of thiamine metabolism in neurodegenerative diseases (67,68).…”
Section: Synthesis Accumulation and Hydrolysis Of Thtp In Differentmentioning
confidence: 99%
“…Such a mechanism could help to better understand the events involved in the onset of neurodegenerative diseases (64). It is therefore interesting to point out that thiamine deficiency has been shown to exacerbate the pathology of Alzheimer disease (63,65,66) and that there are dysfunctions of thiamine metabolism in neurodegenerative diseases (67,68).…”
Section: Synthesis Accumulation and Hydrolysis Of Thtp In Differentmentioning
confidence: 99%
“…While one study reported normal total blood thiamine levels in patients with Alzheimer's dementia [15], others showed decreased levels in plasma or erythrocytes [16], [17]. ThDP levels are decreased in postmortem brains of patients with Alzheimer's disease [18], [19] and frontal lobe degeneration of the non-Alzheimer's type [20].…”
Section: Introductionmentioning
confidence: 99%
“…Methylphenidate has been studied as an adjuvant medication for the treatment of depression and apathy in various disorders (Marin et al, 1995; Chatterjee and Fahn, 2002). Analyses of the neurochemical correlates of FTD based on autopsy tissue have generally implicated deficits in DA and NA neurotransmission (Bettendorff et al, 1997; Francis et al, 1993; Gilbert et al, 1988; Nagaoka et al, 1995; Sjogren et al, 1998; Sparks and Markesbery, 1991). For example, Sjogren et al (1998) reported a significant reduction in the CSF concentration of homovanillic acid, a major metabolite of DA, in a large sample of frontotemporal dementia cases.…”
Section: Introductionmentioning
confidence: 99%